Becoming an insider in a virtual environment : key elements of successful remote onboarding - Blöndal, Satu Vaara (2021)
Employee onboarding is a process enabling the new employee to become a productive member of the company. Previous research indicates that the process is most successful in an office environment. The social distancing and other restrictions set to suppress the Covid19 pandemic have forced companies to change and redesign their business processes to make them executable in a remote working environment, also impacting the onboarding process. This qualitative case study seeks to understand and describe collectively the remote onboarding process participant experiences in a fast-growing case company providing software as service (SaaS) solutions for digital trade in Europe. The study focuses on analyzing the key elements of successful onboarding and the roles of the process participants. Empirical data is collected from the new employees, their mentors, leaders, and cross-team support services using semi-structured interviews. The transcribed interview data is analyzed and organized using thematic analysis with a data matrix format to identify codes and repeating themes. The results are strongly framed by the company growth and the culture of continuous improvement and social, family-like connection. Aligning with existing theories, the identified four key themes of successful onboarding in the case company focus on process, suitable fit, connection, and clarification. Virtual and office-based onboarding key elements are mostly the same; however, the importance and challenges of specific parts differ. The roles of the new hire and a mentor are seen as key roles, supported by the overall team, leader, and cross-company support teams. Results indicate that digitalization, clear processes, and a good fit for hire are seen as important in remote onboarding. Establishing a social connection is seen as challenging. The need for face-to-face interaction to deepen the connection and collaboration is brought up, highlighting an interesting field for further research.